2001
DOI: 10.1364/ao.40.006265
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with a genetic algorithm for structural design of cemented doublets with prespecified aberration targets

Abstract: The authors use a genetic algorithm in the structural design of cemented doublets in accordance with a prespecified set of Gaussian characteristics and primary aberration targets. Actual glasses are taken as variables. Suitable modifications in the algorithm are sought with which to explore the solution space in search of the global as well as useful local optima. Some illustrative examples of structural design are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Using methods given in [2,[21][22][23][24][25][26][27][28][29], we can determine the radii and refractive indices of the lenses from which the individual elements will be composed of. Our design may serve as the starting point for further optimization using optical system design software such as ZEMAX, OSLO, etc.…”
Section: Seidel Aberration Coefficientsmentioning
confidence: 99%
“…Using methods given in [2,[21][22][23][24][25][26][27][28][29], we can determine the radii and refractive indices of the lenses from which the individual elements will be composed of. Our design may serve as the starting point for further optimization using optical system design software such as ZEMAX, OSLO, etc.…”
Section: Seidel Aberration Coefficientsmentioning
confidence: 99%
“…Each design modified by these operators is re-optimized with traditional local search algorithms. Since 1996, several papers have been published on the use of bit string GAs [19,20], real-valued GA [21][22][23] or ES [22,24] for the optimization of a fixed number of real-valued parameters. Results presented in [21] are apparently very good, with the successful automatic design of large-scale lens systems composed of more than ten parts with real-valued GA, and experiments on the use of Pareto optimal selection strategy for multiobjective optimization [25].…”
Section: Lens System Optimizationmentioning
confidence: 99%
“…Practical implementation of this algorithm for structural lens design problems has already been reported in our recent publications, and we refer to them for details. 28,29 When we tried to adopt the algorithm utilized for structural design of doublets to the present problem, it was noted that most optimization runs were giving rise to premature stagnation problems. Further investigations revealed that it was being caused by rapid loss of genetic diversity in the population during the early phases of the optimization run, so much so that crossover operations were not effective in yielding better results.…”
Section: Optimum Values For Threshold Genetic Diversity and Mutation mentioning
confidence: 99%
“…The role of these parameters in enhancing performance of the genetic algorithm has been dealt with in detail in our earlier reports. 28,29 The effect of the genetic diversity criteria, as enunciated in the last section, was manifest by a significant increase in acceleration of convergence of the optimization algorithm, so much so that in most optimization runs, about 100 generations were adequate to obtain the optimum solution. Table 1 gives a selected list of 15 cemented triplets with zero aberration targets.…”
Section: Solution Numbermentioning
confidence: 99%